Vegetation on the chordae and papillary muscle of the mitral valve: a diagnostic and therapeutic enigma - Khawaja, Rizwan Ali; Muhammad Ahmed Tamiz; Fateh Ali Tipoo Sultan (Journal of the Pakistan Medical Association, 2026)
Vegetations on the high-pressure side of the mitral valve, particularly the chordae tendineae, are rare. We report two cases of infective endocarditis (IE) with atypical presentations. Case 1: A 34-year-old male with pulmonary aspergilloma, who presented with fever and respiratory distress. Blood cultures grew Staphylococcus species, and echocardiography revealed a 16 × 8 mm vegetation on the mitral valve chordae. Surgery was deferred due to disseminated fungal infection, and the patient improved with antimicrobial therapy. Case 2: A previously healthy 36-year-old male presented with fever, vomiting, dyspnoea, and headaches. Blood cultures were positive for Methicillin-resistant Staphylococcus aureus (MRSA), and echocardiography detected a 13 × 7 mm vegetation on the mitral valve chordae. The patient responded well to intravenous antibiotics, with complete resolution on follow-up. These cases highlight the need for high clinical suspicion, thorough imaging, and individualised management strategies in atypical presentations of infective endocarditis. Keywords: Infective endocarditis, Chordae vegetation, Echocardiography, Staphylococcus species, Fungal endocarditis, Valve dysfunction.